Lactylation in CNS disorders: mechanisms, cellular function, and disease relevance - Tian, Jiaxin; Zhang, Tongyu; Zhang, Ruidan; Hao, Sijia; Dong, Jingyu; Chen, Yiyan; Zhou, Jinpeng; Tian, Yang (Frontiers in Cell and Developmental Biology, 2025)
Lactate, as a metabolic product or energy substrate, participates in various neurological processes within the physiological and pathological frameworks of the central nervous system (CNS). The groundbreaking application of multi-omics integration technologies has unveiled a novel role for lactate: lactylation, a unique post-translational modification (PTM) that covalently attaches lactate groups to lysine residues on proteins. This process precisely regulates protein function and gene expression, profoundly influencing the progression of various diseases. The lactylation process is meticulously regulated by a variety of key enzymes and metabolic pathways, forming a dynamic and intricate modification network. In this review, we summarize the key enzymes involved in lactylation, specifically “Writers,” “Erasers,” and “Readers.” Furthermore, we systematically categorize lactylation observed in various cell types within the CNS and investigate its multifaceted roles in pathological processes, including neurodegenerative diseases, brain tumors, and brain injuries. By consolidating the latest research findings in this field, our review aims to highlight the significance of these discoveries for future research and explore their potential for translational applications.